Schistosoma mansoni Egg-Released IPSE/alpha-1 Dampens Inflammatory Cytokine Responses via Basophil Interleukin (IL)-4 and IL-13 - Knuhr, Katrin; Langhans, Kristina; Nyenhuis, Sandra; Viertmann, Kerstin; Kildemoes, Anna M. Overgaard; Doenhoff, Michael J.; Haas, Helmut; Schramm, Gabriele (Frontiers in Immunology, 2018)
Schistosomes control inflammation in their hosts via highly effective mechanisms such as induction of Tregs, Bregs, and alternatively activated macrophages (AAMs). Notably, IPSE/alpha-1, the major secretory product from Schistosoma mansoni eggs, triggers basophils to release interleukin (IL)-4 and IL-13. Both cytokines are essential for AAM induction, suggesting an important role for IPSE/alpha-1 in inflammation control. Here, we show by in vitro co-culture experiments that IPSE/alpha-1-induced basophil IL-4/IL-13 inhibited pro-inflammatory cytokine release from human LPS-activated monocytes. This effect was cell/cell contact-independent but dependent on IL-4, since it was abrogated in the presence of anti-IL-4 antibodies. Importantly, the IPSE/alpha-1-induced IL-4/IL-13 release from basophils was amplified in the presence of LPS. Moreover, monocytes co-cultured in the presence of LPS with IPSE/alpha-1-stimulated basophils adopted an AAM-like phenotype as assessed by elevated expression of CD206 and CD209. The putative in vivo relevance of these findings was supported by immunohistological staining of S. mansoni-infected murine tissue revealing close physical contact between IPSE/alpha-1 and basophils in schistosome egg granulomas. Taken together, we found that IPSE/alpha-1 dampens inflammatory cytokine responses by triggering basophil IL-4/IL-13, in particular in the context of TLR activation, thereby turning inflammatory monocytes into anti-inflammatory AAMs. This might represent a mechanism used by schistosomes to control inflammation in the host.